2011
DOI: 10.1254/jphs.10319fp
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Effects of AS1892802, a Rho Kinase Inhibitor, on Osteoarthritic Disorders in Rodents

Abstract: Abstract. The effects of AS1892802, a selective Rho-associated coiled coil kinase (ROCK) inhibitor, on knee cartilage damage and pain behavior were examined in a rat model of osteoarthritis (OA). Monoiodoacetate (MIA) was intraarticularly injected into the right knee joints of rats. ROCK I and II mRNA levels increased in knee joints of MIA-injected rats. Our newly synthesized ROCK inhibitor, AS1892802, was injected into the ipsilateral knee or administered p.o. for 3 weeks. The compound dose-dependently and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Several authors have reported that ROCKi treatment increases glycosaminoglycan synthesis and expression of chondrogenic marker genes in mouse chondrocytic ATDC5 cells (30,31). The ROCK inhibitor AS1892802 prevents cartilage damage in a rat osteoarthritic disorder model (37). .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that ROCKi treatment increases glycosaminoglycan synthesis and expression of chondrogenic marker genes in mouse chondrocytic ATDC5 cells (30,31). The ROCK inhibitor AS1892802 prevents cartilage damage in a rat osteoarthritic disorder model (37). .…”
Section: Discussionmentioning
confidence: 99%
“…Conditional knock-down of Vegf attenuates surgically-induced osteoarthritis in mice, with intra-articular anti-VEGF antibodies as well as oral administration of the VEGFR2 kinase inhibitor Vandetanib suppressing osteoarthritis progression 33 . In a rat model of osteoarthritis, a rho kinase inhibitor was found to reduce knee cartilage damage 34 . Finally, there is a well-established effect of smoking on osteoarthritis 9,35 .…”
Section: Candidate Therapeutic Compoundsmentioning
confidence: 99%
“…In the MIA-induced knee OA model, ABC294640 57 , a selective inhibitor of sphingosine kinase-2; AS1892802 58, 59 , which rarely penetrates the central nervous tissue and is a selective Rho kinase inhibitor; and MEN16132 60 , a kinin B(2) receptor antagonist, significantly improved weight bearing of the injected limb and alleviated cartilage degradation. Systemic co-administration of the selective positive allosteric modulator NS-9283 enhanced the analgesic potency of the nicotinic acetylcholine receptor (nAChR) α4β2 agonist ABT-594 5-fold 61 .…”
Section: Peripheral Mechanismsmentioning
confidence: 99%